Computational Biomechanics for Medicine Fundamental Science and Patient-specific Applications - Doyle, Barry; Miller, Karol; Wittek, Adam; Nielsen, Poul M.F (Springer New York : Imprint: Springer, 2014)
One of the greatest challenges facing the computational engineering community is to extend the success of computational mechanics to fields outside traditional engineering, in particular to biology, the biomedical sciences, and medicine. The Computational Biomechanics for Medicine titles provide an opportunity for specialists in computational biomechanics to present their latest methodologies and advancements. This latest installment comprises nine of the latest developments in both fundamental science and patient-specific applications, from researchers in Australia, New Zealand, USA, UK, France, Ireland, and China. Some of the interesting topics discussed are: cellular mechanics; tumor growth and modeling; medical image analysis; and both patient-specific fluid dynamics and solid mechanics simulations.